Coupled model for microbial growth and phase mass transfer in pressurized batch reactors in the context of underground hydrogen storage - Strobel, Gion; Hagemann, Birger; Lüddeke, Christian Truitt; Ganzer, Leonhard (Frontiers in Microbiology, 2023)
A rising interest in a strong hydrogen economy as a part of the future net-zero economy results in an increasing necessity to store hydrogen as a raw material or an energy carrier. Experience and studies show that storing hydrogen in deep underground sites could enable microbial conversion of hydrogen. To predict and examine the loss of hydrogen, laboratory studies and analysis are essential. A growth model is required to interpret batch or chemostat experiments. With this model, the parameters of microbial growth and the conversion of hydrogen can be specified. This study presents experiments with methanogens and a hydrogen/carbon dioxide gas mixture performed in batch reactors. Further, the microbial growth was modeled by a double Monod model with hydrogen and carbon dioxide as the limiting substrates. As the amount of carbon dioxide dissolved in the water phase can not be neglected, both phases were considered in the proposed model. The mass-transfer rate between the gas and water phase was implemented by a linear relation including the concentrations in both phases and the mass-transfer coefficient. With the resulting coupled model, it was possible to match the pressure behavior in the reactor and conclude the microbial growth kinetics. Two types of methanogenic species were tested to validate the model. The impact of the mass transfer coefficient was studied to derive the growth behavior in porous media. The growth rate and yield coefficient were concluded based on the mathematical model and the experimental data.